Analytical and experimental studies on stress capacity with modified wood members under combined stresses - Abdolzadeh, H.; Ebrahimi, Gh.; Layeghi, M.; Ghassemieh, M. (Maderas. Ciencia y Tecnología, 2025)
The stress capacity of joints made of modified wood members under loading can be affected by design of joints and type of adhesive. Hence, these factors were addressed in this study by assessment of stress capacity variations in corner joints under diagonal applied compressive load induced combined stresses. The joints with mitered and butted design were constructed by application of epoxy and polyvinyl acetate (PVAc) adhesives from furfurylated wood samples with two weight percentage gains (WPGs), i.e., 20% as low level and 60% as high level. Results indicated that stress capacity in both corner joints was not significantly decreased with increasing polymerization of furfuryl alcohol (FA) in wood. Despite the high compression strength in mitered joint, the induced compression stresses were low in comparison with butted joint. The stress capacity in mitered joint bonded with epoxy adhesive enhanced with increasing the level of furfurylation. This was true for shear stress parallel to grain as well. Generally, it could be concluded that mitered joint made of furfurylated members and bonded with epoxy adhesive would be stronger than other corner joints.